2008
DOI: 10.3806/ijktr.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise combined with KAATSU during simulated weightlessness

Abstract: The application of a gravity-specific stress (e.g. LBNP), in combination with exercise, prevents cardiovascular deconditioning in space flight. KAATSU training is a method to induce blood pooling in capacitance vessels by restricting venous return (as with LBNP) and which when combined with lowintensity resistance (RE) exercise produces remarkable muscle mass and muscle strength gains. The purpose of this study was to investigate the hemodynamic and neurohumonal responses induced by KAATSU in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Additionally, previous studies have demonstrated that the application of BFR in the absence of exercise is effective at attenuating both muscle atrophy and muscle strength decreases as the result of limb immobilization [20,21,42]. Therefore, since we observed that BFR exercise induced muscle swelling up to 75 min post-exercise, these findings seem to support the previous hypothesis that an increased muscle swelling response observed with BFR exercise may stimulate hypertrophic response normally observed with this training modality [22].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, previous studies have demonstrated that the application of BFR in the absence of exercise is effective at attenuating both muscle atrophy and muscle strength decreases as the result of limb immobilization [20,21,42]. Therefore, since we observed that BFR exercise induced muscle swelling up to 75 min post-exercise, these findings seem to support the previous hypothesis that an increased muscle swelling response observed with BFR exercise may stimulate hypertrophic response normally observed with this training modality [22].…”
Section: Discussionsupporting
confidence: 90%
“…Increase in HR was observed in previous studies (14, 16, 17), while Yasuda et al (29) reported no increase in the HR after BFR RE.…”
Section: Discussionmentioning
confidence: 64%
“…Nakajima et al [75] showed that restriction of blood flow reproduces the effects of standing on HR, stroke volume (SV), and norepinephrine release, thus simulating a gravity-like stress during short-duration −6HDT bed rest. Furthermore, Kubota et al [76] demonstrated that BFR resistance exercise during short-duration −6HDT bed rest elicits hemodynamic and neurohumoral responses that approximate a gravity-specific stress on the cardiovascular system. In the before-mentioned study, subjects participated in 24 h of −6HDT bed rest resulting in 4.4% and 7.8% losses of BV and PV, respectively.…”
Section: Reviewmentioning
confidence: 99%